BHUMI IRIGASI KUNO SEBAGAI IDE PENCIPTAAN POT KERAMIK DENGAN SELF WATERING SYSTEM DI UD. TRI SURYA KERAMIK - I Gusti Ngurah Diva Ismayana Tjahjadi; I Made Gede Arimbawa; Ida Ayu Gede Artayani; Rai Gede Wahyudi Putra (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Preservation and protection require real action from all of us, therefore the author chooses the general concept carried by the Terramic Bali company, namely the Bhumi concept. By studying from upstream to downstream in running a company, the author hopes to be able to replicate it as a form of independent work opportunity. Every design that carries the Bhumi concept is accompanied by a design lighter idea. The starting idea for the founding of the Terramic Bali company was ancient irrigation. Adopting the creation method from Gustami Sp, namely: 1) Exploration, 2) Design, and 3) Embodiment, it can be seen that the result of the creation is a company engaged in ceramic crafts with distinctive branding. The Business Model Canvas (BMC) of the Terramic Bali company is a simulation of the author's company in an internship program at the Tri Surya Keramik company. The Tri Surya Keramik company is concerned with a digital marketing system as a surefire solution to the Covid-19 pandemic, one of which is Instagram. The company Terramic Bali produces products based on the Bhumi concept, as a design concept to product embodiment and the concept of Earth Tones color which refers to the company's goal, namely: the Environmental Awareness Movement. The products are named Pengalapan, Jelinjing, Cakangan, and Aungan. Storytelling is a strong asset that is used as a means of promotion and education to customers.